Analisis Pelayanan Kesehatan Melalui Peningkatan Status RSUD Kabupaten Bekasi - Yayan Rudianto (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2016)
This research background of lack of health care in Bekasi, especially in Bekasi District Hospital which was rated C. The research question is how the health service in Bekasi District Hospital and the efforts made to improve the status of Bekasi District Hospital. The results showed that there is still a gap between the realities of the service received with hope